Spatial confinement in laser-induced breakdown spectroscopy. (23rd November 2016) - Li, Xingwen; Yang, Zefeng; Wu, Jian; Wei, Wenfu; Qiu, Yan; Jia, Shenli; Qiu, Aici
Abstract: The spatial confinement of plasma produced by a nanosecond laser is investigated using time resolved spectroscopy, fast imaging, interferometry, and numerical computation. The dynamics of the plasma, depending on shock waves, laser power, and wall distances, are studied. Experimental results confirm that the plasma is constricted by the reflected shock associated with a temperature and density gradient. The peak laser power determines the initial plasma parameters which affect the spectral intensities and the velocity of the reflective shock waves. The wall distance determines the reflection time of the shocks, which in turn influences the time delay of the collision between the two reflective shocks. The numerical results reveal a fast propagation process surrounding the reflective shocks, which indicates that the velocity of the reflective shock wave is influenced by the density of the plasma. The maximum enhancement factor ~5.2 is realized at a delay time of 11.7 µ s under a pulse laser energy of 180 mJ and a wall distance of 9 mm.